2016
DOI: 10.1017/s0033291716000398
|View full text |Cite
|
Sign up to set email alerts
|

Memantine augmentation in clozapine-refractory schizophrenia: a randomized, double-blind, placebo-controlled crossover study

Abstract: BackgroundDysfunction of neuroplasticity due to N-methyl-d-aspartate (NMDA) receptor hypofunction may be a causal factor for memory and executive dysfunctioning in schizophrenia. Deregulation of NMDA transmission in the prefrontal cortex may also explain negative and positive symptoms. Clozapine augmentation with memantine targets altered NMDA receptor-mediated neurotransmission in schizophrenia and showed substantial beneficial effects on several symptom domains in a small proof-of-concept study. We evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 73 publications
0
59
0
1
Order By: Relevance
“…In addition to the study conducted by Veerman et al mentioned in results [34], De Lucena et al reported, in a letter to editor, the efficacy of memantine as add-on therapy to clozapine with large effect sizes for overall symptoms, positive symptoms, negative symptoms, and global cognitive functioning in patients with partial remission of negative symptoms of schizophrenia [46]. In the same study it has been further hypothesized that BDNF may play a role in the effect of memantine in patients with schizophrenia, but inconsistent results have been found [46].…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In addition to the study conducted by Veerman et al mentioned in results [34], De Lucena et al reported, in a letter to editor, the efficacy of memantine as add-on therapy to clozapine with large effect sizes for overall symptoms, positive symptoms, negative symptoms, and global cognitive functioning in patients with partial remission of negative symptoms of schizophrenia [46]. In the same study it has been further hypothesized that BDNF may play a role in the effect of memantine in patients with schizophrenia, but inconsistent results have been found [46].…”
Section: Discussionmentioning
confidence: 82%
“…The positive effects of memantine augmentation to clozapine may be linked to their conjunct action on NMDA receptors. This combination modulates glutamatergic neurotransmission at multiple levels [45], with clozapine inducing both upregulation of -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors and NMDA receptors [34]. Schaefer et al 2007 described a memantine-mediated decrease of clozapineinduced weight gain using an on-off-on design with a significant increase of weight after discontinuation and again a substantial weight loss after reexposition with memantine [39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations